Pengaruh Dukungan Atasan, Internal Locus of Control dan Optimisme terhadap Job Insecurity - Siti Nur Azizah (Valid: Jurnal Ilmiah, 2020)
This study aims to look at the effect of internal locus of control, optimism and superiors' support for job insecurity as well as to see whether work duration moderates the effect of locus of control on job insecurity on outsourced employees at PT ISS. This research is a quantitative study with descriptive design. Research respondents are outsourced employees of PT. ISS Kebumen with a total of 65 people. Data is processed with the help of SPSS. The analytical method used in this research is multiple linear regression analysis statistical test results, internal locus of control does not affect job insecurity. Whereas superiors' support and optimism variables have a significant negative effect on job security. This encourages management to pay attention to superiors on employees and encourage them to always be optimistic by providing physical guarantees that involve supervisors and supervise well